TRADISI KAWIN COLONG PADA MASYARAKAT OSING BANYUWANGI PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Wagianto, Ramdan (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Marriage is a sunnatullah which its conditions is determined by religion. However, the existence of marriage becomes disturbed when faced with the matter of tradition, such as the tradition of colong marriage in the Osing Banyuwangi community. This matter is because this tradition has no comprehensive formulation within nas, including alquran, sunnah, as well as ijima’. The colong marriage is a form of making a marriage proposal with traditional Osing wasilah. However, this marriage tradition creates social tension in the community such that there are some who feel aggrieved. There are several factors causing this situation, including: disagreement by parents, nyepetaken lakon, fear of a proposal being rejected, and different social statuses and economic levels. In Islamic law sociology with the theory of al-‘urf approach, consider that the colong marriage still considered of legitimate urf.[Perkawinan merupakan sunnatulllah yang ketentuannya telah ditetapkan dalam agama. Akan tetapi, eksistensi perkawinan menjadi terusik ketika dihadapkan dengan persoalan tradisi, seperti tradisi kawin colong pada masyarakat osing Banyuwangi. Hal tersebut dikarenakan tradisi ini tidak ada rumusan yang komprehensif di dalam nas baik Alquran, Sunnah maupun ijma’. Kawin colong merupakan bentuk peminangan dalam perkawinan dengan wasilah adat osing. Namun, tradisi kawin ini menyebabkan ketegangan sosial di masyarakat, sehingga ada pihak yang merasa dirugikan. Ada beberapa faktor penyebabnya, diantaranya adalah tidak disetujui oleh orang tua, nyepetaken lakon, takut lamaran ditolak dan perbedaan status sosial dan tingkat perekonomian. Sosiologi Hukum Islam dengan pendekatan teori al-‘urf, memandang kawin colong masih tergolong ‘urf yang sahih.]